"Responsory" / Gloss between Verlaine and Darío - de Villena, Luis Antonio (Tropelías: Review of Literary Theory and Comparative Literature, 1997)
When Verlaine dies, Rubén Daría writes a poem as tribute to his died master (189ó). But he does not limite himself to the ususal poem-panegyric. Darío -the luxurious Darío of Profane proses- evokes the satire Paul Verlaine to identify himself with his world and his life. And so Responsory (it is the theme of this paper) turns into a splendid psicography that defines and penetrates the worlds -exalted, tenebrous and luminous- of both poets. Simbolists of major tone, magnificent creators that, as all the greats, looked for tradition and rebellion -advance- at the same time.
Keywords: Rubén Darío; Paul Verlaine